2010
DOI: 10.1177/0960327110363333
|View full text |Cite
|
Sign up to set email alerts
|

Experimental impact of aspirin exposure on rat intestinal bacteria, epithelial cells and cell line

Abstract: Aspirin, a commonly used therapeutic non-steroidal anti-inflammatory drug (NSAID) is known to cause gastric mucosal damage. Intestinal bacteria having a regulatory effect on intestinal homeostasis play significant role in NSAID-induced intestinal injury. Bacteria and specific cell lines are considered to be suitable for toxicity screening and testing of chemicals. Therefore, to evaluate and compare in vitro toxicity, cultures of rat intestinal epithelial cells (IEC), isolated bacteria and IEC-6 cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…However, the exact mechanisms through which aspirin reduces risk of colorectal neoplasia and the molecular targets of aspirin in the context of CRC prevention have not been established. Data from animal studies have revealed that aspirin influences the gut microbiome either indirectly via an immune mechanism or directly via a local effect 10‐14 . Moreover, it was shown in humans that aspirin and other salicylate may inhibit the growth of pro‐inflammatory bacteria in a dose‐dependent manner 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanisms through which aspirin reduces risk of colorectal neoplasia and the molecular targets of aspirin in the context of CRC prevention have not been established. Data from animal studies have revealed that aspirin influences the gut microbiome either indirectly via an immune mechanism or directly via a local effect 10‐14 . Moreover, it was shown in humans that aspirin and other salicylate may inhibit the growth of pro‐inflammatory bacteria in a dose‐dependent manner 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The intake of high-dose paracetamol (>2 g per day) and/or NSAIDs for musculoskeletal pain [ 3 , 4 ] has adverse effects on GIT physiology and morphology further inducing GIT symptoms reported by these patients [ 2 , 5 , 6 , 7 , 8 ]. GIT commensal microbial viability and growth may potentially be disrupted with the use of these medications, as demonstrated in animal and in vitro studies [ 9 , 10 , 11 ]. The association between GIT dysfunction, altered microbial profiles and the inconsistent clinical results for compounds such as glucosamine and green-lipped mussel extract in treating symptoms of OA has only recently been alluded to [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin and some NSAIDs, including indomethacin, influence intestinal bacteria [57][58][59][60] . Indomethacin might exert some impact on intestinal microbiota in our study, as there was an increase in breath methane after the treatment in 5/6 pigs from the indomethacin group.…”
Section: Discussionmentioning
confidence: 99%